Table tennis experts outperform novices in a demanding cognitive-motor dual-task situation - Schaefer, S.; Scornaienchi, D. (Journal of Motor Behavior, 2020)
Theories on motor skill acquisition predict that earlier learning stages require more attention, which should lead to higher cognitive-motor dual-task interference in novices as compared to experts. Expert and novice table tennis players returned balls from a ball machine while concurrently performing an auditory 3-back task (working memory). The groups did not differ in 3-back performance in the single task. Cognitive dual-task performance reductions were more pronounced in novices. A similar pattern emerged for the number of missed balls in table tennis, except that experts outperformed novices already in the single task. Experts consistently showed costs of about 10%, while novices showed costs between 30% and 50%. The findings indicate that performances of novices suffer considerably in motor-cognitive dual-task situations.